Pembelajaran Berbasis Proyek Menggunakan Software Matematika Geogebra Terhadap Kemampuan Komputasi Siswa - Khairiah, Dianny Rachma; Yahfizham (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The aim of this research is to determine students' computing abilities in using GeoGebra mathematics software and understand its impact on students' conceptual understanding of learning outcomes. This research also aims to evaluate the increase in students' motivation, logical thinking skills and mathematical representation abilities. The results of the research show an increase in competency for both students and teachers at Dinamika Vocational School, Tegal City regarding the use of mathematical computing programs. This increase attracted the interest and desire of the principal of SMK Dinamika Kota Tegal to implement the results of the training program that had been implemented. It is hoped that the findings of this research can encourage wider implementation of GeoGebra in the mathematics education curriculum. The conclusion of this research is that this application improves students' mathematical computing abilities, facilitates visualization and interactiveness of mathematical concepts.